ЗАСТОСУВАННЯ КОНЦЕПЦІЇ SMART GRID З МЕТОЮ ЗБІЛЬШЕННЯ ПРОПУСКНОЇ ЗДАТНОСТІ ЛІНІЇ ЕЛЕКТРОПЕРЕДАЧІ НАДВИСОКОЇ НАПРУГИ - Кучанський, В.В. (Інститут електродинаміки Національної академії наук України, 2020)
It is shown that the use of controlled shunt reactors in the extra high-voltage power lines allows transmitting capacitance. Inductance values of controlled shunt reactors at which maximum permissible power values are determined. The change in the degree of charge power compensation in the use of controlled shunt reactors is analyzed. It is determined that at a certain inductance range, the values of the allowable power of the transmission line remain unchanged. The use of the Smart Grid concept has allowed the high-voltage power lines to be upgraded to the requirements of flexible AC power lines. The above results indicate that controlled shunt reactors are promising and are required to control the parameters of the power systems. References 15, figures 3, table.